Energy Transport at the Micro/Nanoscale (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue focuses on recent technology developments in the measurement of the thermal conductivity/diffusivity of micro/nanoscale materials, including 2D materials, micro/nanoscale wires/fibers, and nanostructured materials. Techniques such as photothermal, transient electrothermal, and energy transport state-resolved Raman have been reviewed in great detail.